Twenty Years of the SENTRY Antifungal Surveillance Program: Results for Candida Species From 1997–2016 - Pfaller, Michael A; Diekema, Daniel J; Turnidge, John D; Castanheira, Mariana; Jones, Ronald N (Open forum infectious diseases, 2019)
Abstract Background The emergence of antifungal resistance threatens effective treatment of invasive fungal infection (IFI). Invasive candidiasis is the most common health care–associated IFI. We evaluated the activity of fluconazole (FLU) against 20 788 invasive isolates of Candida (37 species) collected from 135 medical centers in 39 countries (1997–2016). The activity of anidulafungin, caspofungin, and micafungin (MCF) was evaluated against 15 308 isolates worldwide (2006–2016). Methods Species identification was accomplished using phenotypic (1997–2001), genotypic, and proteomic methods (2006–2016). All isolates were tested using reference methods and clinical breakpoints published in the Clinical and Laboratory Standards Institute documents. Results A decrease in the isolation of Candida albicans and an increase in the isolation of Candida glabrata and Candida parapsilosis were observed over time. Candida glabrata was the most common non–C. albicans species detected in all geographic regions except for Latin America, where C. parapsilosis and Candida tropicalis were more common. Six Candida auris isolates were detected: 1 each in 2009, 2013, 2014, and 2015 and 2 in 2016; all were from nosocomial bloodstream infections and were FLU-resistant (R). The highest rates of FLU-R isolates were seen in C. glabrata from North America (NA; 10.6%) and in C. tropicalis from the Asia-Pacific region (9.2%). A steady increase in isolation of C. glabrata and resistance to FLU was detected over 20 years in the United States. Echinocandin-R (EC-R) ranged from 3.5% for C. glabrata to 0.1% for C. albicans and C. parapsilosis. Resistance to MCF was highest among C. glabrata (2.8%) and C. tropicalis (1.3%) from NA. Mutations on FKS hot spot (HS) regions were detected among 70 EC-R isolates (51/70 were C. glabrata). Most isolates harboring FKS HS mutations were resistant to 2 or more ECs. Conclusions EC-R and FLU-R remain uncommon among contemporary Candida isolates; however, a slow and steady emergence of resistance to both antifungal classes was observed in C. glabrata and C. tropicalis isolates.